(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study delves into the expanding role of physical education (PE) in secondary schools, transcending its traditional focus on physical health to embrace significant impacts on students’ mental well-being and academic performance. Through a comprehensive review of literature and theoretical analysis, it reveals how regular physical activity can mitigate stress, anxiety, and depression among adolescents, while also enhancing cognitive functions crucial for learning, such as concentration and memory. The paper advocates for a holistic approach to PE, proposing policy reforms and strategies to implement inclusive, varied programs that address both mental and academic needs. It underscores the necessity for educational policymakers to reevaluate and enhance PE curricula, highlighting the essential role of physical education in fostering well-rounded student development and academic success.